Refiguring the Poetic Elegy in Music: The Rhetoric of Mourning in Parry's Elegy for Brahms. Issue 3 (8th April 2022) - Allis, Michael
ABSTRACT: Of Hubert Parry's relatively neglected works, his Elegy for Brahms for orchestra (1897) is particularly intriguing. Written to mark Brahms's death, it was not premiered until Parry's own memorial concert in 1918. After contextualizing the work in terms of Parry's clear admiration for Brahms and highlighting significant British orchestral elegies at the turn of the twentieth century, this article suggests how studies of the poetic elegy can be used as a hermeneutic tool to identify a musico-rhetorical structure at the heart of Parry's composition. Specifically, elegiac conventions and devices identified by Peter Sacks as significant features of poetic models (including the use of repetition, elegiac questioning, processional, the division of mourning voices, and the issue of fame and inheritance) can be identified in Parry's musical design. This interdisciplinary approach not only creates a distinctive new reading of Parry's Elegy, but has wider implications for elegiac music in general.